Francisella Tularensis Metabolism and its Relation to Virulence - Meibom, Karin L.; Charbit, Alain (Frontiers in Microbiology, 2010)
Francisella tularensis is a Gram-negative bacterium capable of causing the zoonotic disease tularaemia in a large number of mammalian species and in arthropods. F. tularensis is a facultative intracellular bacterium that infects and replicates in vivo mainly inside macrophages. During its systemic dissemination, F. tularensis must cope with very different life conditions (such as survival in different target organs or tissues and/or survival in the blood stream…) and may thus encounter a broad variety of carbon substrates, nitrogen, phosphor, and sulfur sources, as well as very low concentrations of essential ions. The development of recent genome-wide genetic screens have led to the identification of hundreds of genes participating to variable extents to Francisella virulence. Remarkably, an important proportion of the genes identified are related to metabolic and nutritional functions. However, the relationship between nutrition and the in vivo life cycle of F. tularensis is yet poorly understood. In this review, we will address the importance of metabolism and nutrition for F. tularensis pathogenesis, focusing specifically on amino acid and carbohydrate requirements.